Effectiveness of Teacher Performance at SMA Negeri 1 Kambowa, North Buton Regency - Zelin; Kabiba; Halima (Universitas Muhammadiyah Palu, 2025)
This study aims to find out how effective the performance of teachers at SMA Negeri 1 Kambowa, with the type of conceptual analysis research using qualitative (descriptive) methods. The subjects of this study consisted of 12 people who included school principals, teachers and students. In collecting data, researchers use three methods, namely interviews, observations, and documentation. Interview.Data validity is carried out by triangulating data through source triangulation, method triangulation, and theory triangulation. The results of the study show that the effectiveness of teacher performance is not optimal/maximal considering that there are still obstacles in carrying out their duties and obligations, both when planning the learning process that still lacks understanding in making lesson plans, lack of discipline that causes material delays and lack of firmness of the principal in making decisions when teachers lack discipline and students have low grades that are still in the grade.